2005
DOI: 10.1002/neu.20121
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of an identified motoneuron during metamorphosis: Hormonal influences on the growth of dendrites and axon terminals

Abstract: During metamorphosis of the tobacco hawkmoth Manduca sexta, the femoral depressor motoneuron (FeDe MN) undergoes remodeling of its dendrites and motor terminals. Previous studies have established that remodeling of MNs during metamorphosis is mediated by the same hormones that control metamorphosis: the ecdysteroids and juvenile hormone (JH). During the pupal stage, the ecdysteroids promote adult-specific growth of MNs in the absence of JH, but JH or its synthetic mimics can interfere with ecdysteroid-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
2
0
2
Order By: Relevance
“…It is possible that local environments may play a role. A recent study in Manduca found central versus peripheral hormonal differences affecting axon versus dendrite remodeling (38). However, it remains to be tested whether the ecdysone levels are different in the fly epidermis and the VNC during metamorphosis.…”
Section: C4da Neurons Retain Larval Axons During Dendrite Pruningmentioning
confidence: 99%
“…It is possible that local environments may play a role. A recent study in Manduca found central versus peripheral hormonal differences affecting axon versus dendrite remodeling (38). However, it remains to be tested whether the ecdysone levels are different in the fly epidermis and the VNC during metamorphosis.…”
Section: C4da Neurons Retain Larval Axons During Dendrite Pruningmentioning
confidence: 99%
“…По имеющимся данным литературы, форма двигательных окончаний в мышцах языка у большинства млекопитающих довольно однообразна (Mu and Sanders, 2010). Например, Knittel and Kent (2005), исследовавшие двигательные окончания языка у представителей класса рыб, также отмечает удивительное сходство в их строении.…”
Section: Discussionunclassified
“…Активность мионеврального синапса зависит как от количества терминальных веточек и ядер бляшек, так и от ее размеров. Об этом свидетельствуют работы Knittel and Kent (2005), показавших, что характерной особенностью двигательных окончаний является высокая концентрация и активность локализованных в ней энзимов по сравнению с нервными и мышечными волокнами. При этом Mu et al (2013) подчеркивают, что ферменты, необходимые для специфической деятельности нервных элементов, распределяются преимущественно в производных шванновской глии.…”
Section: Discussionunclassified
“…The somata of the monopolar motoneurons in A1 and A2, for example, move anteriorly into the forming pterothoracic ganglion. The axon terminals of motoneurons, however, remain in persistent, close contact with their muscle targets, even if the muscle undergoes remodeling during metamorphosis (Weeks and Truman, 1986; for review see Consoulas et al, 2000; Knittel and Kent, 2002, 2005). These constraints present a puzzle: How does an axon grow over a long distance when its soma and axon are anchored at both ends?…”
Section: Discussionmentioning
confidence: 99%